Теоретичне моделювання електроприводу подрібнювачів зерна - Смуригін, Володимир Миколайович; Катюха, Анатолій Андрійович (НТУ "ХПІ", 2010)
The problems of modeling of load torque crusher grain on the basis of experimental data. A structural scheme of the formation of load torque. The aspects of a single-phase electric drive, the need to regulate the reactive power when changing the impedance of the capacitor unit by changing the intermediate frequency invert.
Theoretical modeling of electrodrive grain grinders
Keywords: електропривід частотнорегульований; двигун асинхронний; навантаження; момент електромагнітний; потужність реактивна; інвертор напруги